Knowledge integration in transdisciplinary sustainability science: Tools from applied critical realism. (16th December 2021) - Cockburn, Jessica
Abstract: Transdisciplinarity, which seeks to transcend the limits of existing disciplines and the boundaries between science and society, has become a hallmark of sustainability science. Since transdisciplinarity requires researchers to co‐produce knowledge by drawing together diverse knowledge systems, knowledge integration becomes a key challenge. However, the practice of knowledge integration brings to the fore tensions around philosophy, methodology and the role of the researcher. The purpose of this paper is to demonstrate the value of applied critical realism in enabling knowledge integration in transdisciplinary research, and in engaging these important tensions. I introduce tools from applied critical realism to enable knowledge integration across disciplinary and science‐society boundaries in sustainability science. Using an illustrative case of place‐based social‐ecological research from South Africa, I demonstrate the application of these tools. I conclude with a reflection on how they enable reflection on tensions related to philosophy, methodology and researcher positionality, identifying some of the challenges I experienced in putting these tools to work.